The Janus-faced nature of complement in hemodialysis: interplay between complement, inflammation, and bioincompatibility unveiling a self-amplifying loop contributing to organ damage - Canaud, Bernard; Stenvinkel, Peter; Scheiwe, Rebecca; Steppan, Sonja; Bowry, Sudhir; Castellano, Giuseppe (Frontiers in Nephrology, 2024)
In hemodialysis (HD), complement activation, bioincompatibility, and inflammation are intricately intertwined. In the 1970s, as HD became a routine therapy, the observation of complement pathway activation and transient leukopenia by cellulosic dialysis membranes triggered the bioincompatibility debate and its clinical relevance. Extensive deliberations have covered definitions, assessment markers, scope, and long-term clinical consequences of membrane-dependent bioincompatibility reactions. While complement pathways’ interplay with coagulation and inflammation has been delineated, HD’s focus has primarily been on developing more biocompatible membranes using advanced technologies. Recent advances and understanding of the current HD delivery mode (4-hour sessions, thrice weekly) suggest that factors beyond membrane characteristics play a significant role, and a more complex, multifactorial picture of bioincompatibility is emerging. Chronic activation of the complement system and persistent low-grade “uremic inflammation” in chronic kidney disease (CKD) and HD lead to premature inflammaging of the kidney, resembling aging in the general population. Cellular senescence, modulated by complement activation and the uremic milieu, contributes to chronic inflammaging. Additionally, the formation of neutrophil extracellular traps (NETs, process of NETosis) during HD and their biological activity in the interdialytic period can lead to dialysis-induced systemic stress. Thus, complement-inflammation manifestations in HD therapies extend beyond traditional membrane-related bioincompatibility consequences. Recent scientific knowledge is reshaping strategies to mitigate detrimental consequences of bioincompatibility, both technologically and in HD therapy delivery modes, to improve dialysis patient outcomes.